EFFICIENCY OF INFRASTRUCTURAL COMPONENTS OF THE RAILWAY TRANSPORT MAINTENANCE SYSTEM - Одєгов, Микола; Крашенінін, Олександр; Шапатіна, Ольга; Войтенко, Володимир (SWorldJournal, 2022)
Traditional approaches to assessing the effectiveness of the infrastructure of railway units do not fully take into account the types of systems that make up this infrastructure. This is that systems (locomotives, cars, machines, buildings, subdivisions o